Bernstein-type inequalities for L-splines - Babenko, V. F.; Ligun, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
New Berhstein-type inequalities are obtain for 2π-periodic L -splines associated with a differential operator L_τ (D) of degree r with fixed real coefficients.